FACTORS FOR EVALUATION OF DIFFICULTY OPERATIONAL ENVIRONMENT IN EMERGENCY SITUATIONS SOCIAL CHARACTER, RESULTING MASS ACTIVITY OF CITIZENS - Batsamut, V. М.; Drobaha, G. А. (Honor and Law, 2019)
According to the analysis of events that have passed during the Revolution of dignity in Kiev, updated list of important factors that define the complexity of the operational environment in the context of mass activity of citizens. The method of analysis of hierarchies held their ranking.